The Intertext of l. Annensky in N. Gumilev’s Collection of Poems Quiver - Vidugirytė, Inga (Respectus Philologicus, 2003)
The intertext of Annensky in Gumilev’s Quiver reveals itself as a complex of different references to the creative work and the personality of Annensky. These references in Gumilev’s poetry could be discussed in two aspects. Both of them are displayed in the first poem of the collection - , To the Memory of Annensky". One of these aspects is related with the notion of voice which refers to the poetry of Annensky and to its specific characteristics. It also challenges Gumilev’s opposition which manifests itself as a polemic development of some Annensky’s poetic motifs in , Evening" and , Stanzas". The second aspect of , Annensky’s text" in Quiver refers to the personality of Annensky and emerges as a complex of motifs related with Euripides. This complex participates in Gumilev’s reflections of his own life in poems , I’m polite to the modern life ... ", , What a strange tenderness ... ", and , I haven’t lived, I have languished ... ". The motif of opposition to the present time in these poems is comparable to the same notions in Annensky’s thoughts on his own role and the role of Euripides in ancient Greece. It is worth noting that Gumilev’s attitude to Annensky’s person is related with a new tendency of Gumilev to create a specific autobiographical discourse which reveals itself as a narration of his own life. In this perspective, , the text of Annensky" could be understood as a myth of Annensky - one among other Gumilev’s myths.